(3Gdbhd GdJGe aj aVd GdQei HGdSgGes - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QGei GdYOh HGdSge GdYQHi GdGTQa hHYO adeG cGf GdQei HGdSgGe ef CLd CfhGY GdaQhSjI dchfg ai GdYOh Cfci hCHdZ ai Mdhd GdEfJbGe s
(3BNQgG (B:s
(3bGd abHd GHf GdeHGQc LHgI GdaVjd QMegeG Gddg hbGd jG eYde GdNHQ ef jMS gPG ZjQc BNQ Gdbhd GdJGe hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B150s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1363s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs